104 Sex hormonal profile during the development from endometrial hyperplastic disease to endometrial cancer. (18th September 2019) - Shi, Y; Chen, X; Yang, B
Abstract : Objectives: To explore the endocrine profiles during the development from endometrial hyperplasitic disease to endometrial cancer (EC). Methods: A prospective study in the Obstetrics and Gynecology Hospital of Fudan University from September 2011 to Nov 2018 was conducted. A total of 1874 cases were enrolled, including 764 cases of healthy women, 145 cases diagnosed with disordered proliferative endometrium (DPE), 250 cases with simple hyperplasia (SH), 200 cases with complex hyperplasia (CH), 259 cases with endometrial atypical hyperplasia (EAH), 256 cases of EC. Profiles of BMI and sex hormone levels (Estrodiol, P, T, FSH, LH, SHBG and E2/SHBG) were analyzed and compared in different groups. Multiple linear regression analysis was done to control for the counfounding factor, age. Results: Physiologically, text-book hormonal profiles were confirmed with our study in control group as shown below. Estradiol elevation only took place in pre-cancerous stage. However, progesterone trend is a bit delayed, the significant difference totally vanished until the stage EEC G2, which stage is also a contraindication for conservative treatment with high potency progestins. No significant difference was found for free estrogen level (FEI) in different groups compared with the control. BMI gradually increases and peaks at EEC (G1, G2), and this group of patients was the only group with both median and mean BMI> 25kg/m2, aka, overweight. Conclusions: "Guider Effect Model" was hypothesized that E2 in here is as a guider in theater, once cancer cells gain carnogenic mutation, (seated in cancer), the guider just left immediately, while other hormones will be interpreted in presentation d/t word limit